Enhancing business performance of small and medium-sized travel enterprises in Ho Chi Minh city, Vietnam - HUYNH, Tam Minh; CHU, Hiep Bao; NGUYEN, Ha Hong (Edelweiss Applied Science and Technology, 2025)
The purpose of this study was to investigate the innovation capabilities in tourism businesses in Ho Chi Minh City, Vietnam. Data for the study was gathered between May 4, 2024, and October 12, 2024, by surveying 443 managers who are directly in charge of tourism businesses in Ho Chi Minh City and who are also members of the Board of Directors. The authors, inheriting previous research, identified the most often observed variables for each factor using confirmatory factor analysis (CFA), and the SEM model also supported the idea that innovation capability acted as a mediator between the aforementioned factors. Based on these findings, the study has recommended managerial changes to enhance future investments in fostering market orientation, digital marketing, CRM, and innovation capabilities in order to attain strong business performance in Ho Chi Minh City, Vietnam’s tourism SMEs.